Variable-rate coding with constant BER for NOMA via multilevel IRA coding - Chi, Yuhao (2020)
In this correspondence paper, a variable-rate coding scheme is proposed for an uplink NOMA system. Specifically, each user employs a multilevel irregular repeat-accumulate (IRA) coding scheme, which consists of multiple common component IRA encoders. The variable-rate coding scheme is realized by flexibly adjusting the number of component IRA encoders allocated to each user. We design this common component IRA encoder based on extrinsic information transfer analysis to achieve an overall good multi-user decoding performance. The advantages of our proposed scheme are as follows: first, simple implementation of rate variation, second, flexible design of multilevel IRA coding, i.e., the well-designed component IRA encoders does not need to be re-designed when any user changes its rate, third, fair decoding convergence of each user, and finally, capacity-approaching performance.